Assessing Customer-Based Brand Equity and Brand Competitiveness of an Electronic Company in Bangladesh - Tanu, Dil Ruba; Ahmed, Selim; Latif, Wasib Bin (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
This study measures brand equity and brand competitiveness of the Minister brand in Bangladesh. The present study investigates significant difference or conformance on five dimensions of brand equity, namely perceived quality, brand awareness, brand association, brand affection, and brand loyalty based on customers’ demographic information such as gender, age, marital status and income. It also identifies significant difference or conformance on brand competitiveness based on demographics. In this study, 500 self-administered survey questionnaires were distributed to customers of Minister in Bangladesh of which 348 useful responses were returned for 69.6% valid response rate. The research data were analysed based on reliability analysis, independent samples t-tests and one-way analysis of variance (ANOVA) using SPSS-23 version software. The research findings indicate that married customers have a better perception of brand loyalty of electronic products compared to single customers. The findings also indicate that customers aged between 21-30 years are more passionate (brand affection) about electronic goods compared to other age groups. The findings are expected to provide guidelines for enhancing the level of brand equity and competitiveness in Bangladesh’s electronic industries as well as other countries.